Wind Influence on Air Rami Estuary Morphology: A Vector Analysis: Pengaruh Angin terhadap Morfologi Muara Air Rami: Analisis Vektor - Oktari Elha Safitri; Supiyati Supiyati; Suwarsono Suwarsono (Universitas Muhammadiyah Sidoarjo, 2023)
Investigating the dynamic Air Rami Estuary in Mukomuko Regency, Bengkulu Province, this study explores the role of wind movement in shaping estuarine morphology. The research aims to discern wind speed and vector direction associated with estuarine changes. Employing field measurements, wind parameters, and estuary imagery from USGS, the investigation reveals wind speeds ranging from 1.630 to 5,210 m/s, averaging 3.153 m/s, predominantly oriented south and southwest. These findings underscore the profound impact of wind dynamics on Air Rami Estuary's shape alterations, advancing our understanding of coastal morphological evolution and resilience. Highlight: Estuarine Wind Dynamics: This study investigates how wind movement influences the morphological evolution of the Air Rami Estuary, shedding light on a crucial coastal process. Wind Speed and Direction: By analyzing wind parameters and vector direction, the research uncovers a range of wind speeds and prevailing orientations, revealing significant insights into estuarine changes. Resilience and Evolution: The findings emphasize the substantial impact of wind dynamics on shaping estuarine morphology, contributing to our broader understanding of coastal resilience and evolution. Keyword: Air Rami Estuary, Wind Movement, Estuarine Morphology, Wind Speed, Coastal Evolution